Smoking, Central Adiposity, and Poor Glycemic Control Increase Risk of Hearing Impairment - Cruickshanks, Karen J. (J Am Geriatr Soc, 2015)
OBJECTIVES: To determine associations between smoking, adiposity, diabetes, and other cardiovascular disease (CVD) risk factors and the 15-yr incidence of hearing impairment (HI). DESIGN: The Epidemiology of Hearing Loss Study (EHLS) is a longitudinal population-based cohort study (1993–95 to 2009–2010). SETTING: Beaver Dam, WI. PARTICIPANTS: Participants in the Beaver Dam Eye Study (1988–90; residents of Beaver Dam, WI ages 43–84 years in 1987–88) were eligible for the EHLS. There were 1925 participants with normal hearing at baseline. MEASUREMENTS: 15-year cumulative incidence of HI (pure-tone average (PTA) of hearing thresholds at 0.5, 1, 2 and 4 kHz > 25 decibels Hearing Level (dB HL) in either ear). Cigarette smoking, exercise, and other factors were ascertained by questionnaire. Blood pressure, waist circumference, body mass index and glycosylated hemoglobin were measured. RESULTS: Follow-up examinations (≥1) were obtained from 87.2% (n=1678; mean baseline age 61 years). The 15-year cumulative incidence of HI was 56.8%. Adjusting for age and sex, current smoking (Hazard Ratio (HR) =1.31, p=0.048), education (<16 yrs; HR=1.35, p=0.01), waist circumference (HR=1.08 per 10 cm, p=0.017), and poorly controlled diabetes (HR=2.03, p=0.048) were associated with increased risk of HI. Former smokers and people with better controlled diabetes were not at increased risk. CONCLUSION: Smoking, central adiposity and poorly controlled diabetes predicted incident HI. These well-known CVD risk factors, suggest vascular changes may contribute to HI in aging. Interventions targeting reductions in smoking and adiposity, and improved glycemic control in people with diabetes, may help to prevent or delay the onset of HI.